Element Analysis and Sustainable Development of Portuguese Architecture - Junxin Song (PT FORMOSA CENDEKIA GLOBAL, 2022)
This paper mainly analyzes the elements of Portuguese architecture. Finally, according to the results of field investigation and historical data analysis, some reference suggestions are put forward from the perspective of cultural heritage protection